Governing universities in post-Soviet countries : from a common start, 1991-2021 - Eckel, Peter D. (Cambridge Education Research., 2023)
University governance is an essential but complex phenomenon, even in countries where institutional-level governance has a long and strong tradition. After the dissolution of the USSR, each of the 15 former Soviet countries developed their own university governance system and this groundbreaking book explores how these countries evolved from the 'common start' of a unified and tightly controlled higher education system, to shaping their own paths in higher education. Each chapter explores a different country, allowing university governance models to be compared and contrasted. The countries provide examples of a variety of different governance models - state-extended, academic focused, internal/external and civic - and the book highlights the advantages and disadvantages of each relative to their context. It also presents innovative frameworks to understand governance effectiveness in terms of autonomy, competition, and capacity. It is essential reading for researchers, students, and policy makers. This title is also available as open access on Cambridge Core.